Analisis Dan Perbaikan Aplikasi UB Bookstore Berdasarkan Aspek Usability (ISO 9241-11) - Harun Christian Bentro; Retno Indah Rokhmawati; Komang Candra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
To achieve the vision of becoming the largest Electronic Publisher in Indonesia, UB Press released UB Bookstore Application. There are 5 processes observed: sign up and sign in process, profile editing process, category and book search process, and book details. Problems in applications that appear on the initial observation include unresponsive navigation, lack of detailed book information, lack of interest in application color, and difficult to finding book and menu navigation. Therefore, there are three basic guidelines used for repairing the application interface. Further, usability testing is done for initial and new design. ISO 9241-11 is used as a standard to measure usability metrics, including Effectiveness, efficiency and satisfaction metrics. The results of the Effectiveness metrics are divided into 3 aspects: Success with 40% improvement, Non Critical Error , and Critical Error which is decreased to 0%. After repairing the application interface, efficiency metric increased to 40% after the interface repair. In the aspect of satisfaction, the new interface design is in grade C and in the